Kashmir in India-Pakistan Relations: Perspectives Pakistan's Nuclear Policy, Background and Development Towards conflict resolution - Souma Tawkeel (International Journal of Science and Society, 2023)
The conflict between India and Pakistan over the Kashmir problem still seems to be an obstacle in their relations. It has been 58 years since the dispute passed, but there is no final agreement that can be accepted by both parties. If 1947 is the independence day of India and Pakistan, then this year is the beginning of the suffering of the people of Kashmir. Pakistan, as the party that has the right to make Kashmir part of its territory, feels the need to continue to raise this issue even though it has to develop nuclear power.